1987
DOI: 10.1099/00221287-133-10-2883
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin-like Enzyme Activity of the Extracellular Membrane Vesicles of Bacteroides gingivalis W50

Abstract: Trypsin-like enzyme activity in spent culture media from 3-d-old batch cultures of Bacteroides gingivalis W50 was measured by using the hydrolysis of Na-benzoyl-L-arginine-p-nitroanilide. The cell-free culture medium was fractionated by differential centrifugation at 10000 g and 75000 g, yielding two particulate fractions and a soluble supernatant fraction. About 80% of the total recoverable activity was associated with the particulate fractions, the remainder being in the supernatant. Electron microscopy of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 23 publications
4
66
1
Order By: Relevance
“…Both enzymes are cell-associated and released into the supernatant of batch cultures of the organism. We cannot yet state whether they are both components of the extracellular vesicle trypsin-like activity (Smalley & Birss, 1987). These data are complementary to those recently presented by Hinode et al (1991) who described the purification of three proteases from the culture supernatant of P. gingivalis 381.…”
Section: Inhibit Ion Of Haemagglu Tinat Ioncontrasting
confidence: 40%
“…Both enzymes are cell-associated and released into the supernatant of batch cultures of the organism. We cannot yet state whether they are both components of the extracellular vesicle trypsin-like activity (Smalley & Birss, 1987). These data are complementary to those recently presented by Hinode et al (1991) who described the purification of three proteases from the culture supernatant of P. gingivalis 381.…”
Section: Inhibit Ion Of Haemagglu Tinat Ioncontrasting
confidence: 40%
“…Most of the trypsin-like activity of P. gingivalis (54,55), including RGP-1, is localized in the extracellular membrane vesicles and cell membranes of invasive strains of the bacteria (Potempa, J., unpublished observation). Hence, RGP-1 should be in contact with PK and HMWK present in periodontal interstitial fluid or plasma leaked into periodontitis sites, thereby producing kallikrein and, ultimately, the liberation of BK from HMWK.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that the HA of B. gingivalis has trypsin-like protease activity and that the site of the molecule participating in the hemagglutination is also involved in the catalysis. Since it has been reported by several researchers including us that B. gingivalis produces protease(s) hydrolyzing synthetic substrates of trypsin-like proteases such as benzoyl-L-arginine p-nitroanilide (BAPA) (2,4,7,10,12,14), it is of great interest from both biochemical and clinical points of view to examine the relationship between the HA and this BAPA-hydrolyzing protease of B. gingivalis. In this report, as a first step, we examined effects of various compounds on the HA and the BAPA-hydrolyzing protease activities in the membrane fraction of B.…”
mentioning
confidence: 99%